Pre-Emptive Law Enforcement Efforts of Community Policing in the Prevention of Terrorism Crimes Based on Justice Values - Munasir, Aco Ardi Andi; Soekorini, Noenik; Astutik, Sri; Cornelis, Vieta Imelda (Transpublika Publisher, 2025)
This research aims to: 1) Analyze the pre-emptive law enforcement efforts of Community Policing in the prevention of terrorism crimes based on the value of justice; 2) Analyze obstacles in efforts to enforce the pre-emptive law of Community Policing in the prevention of terrorism crimes based on the value of justice. The research method used is sociological juridical. The results of the study show that pre-emptive law enforcement efforts in the prevention of terrorism crimes have not been based on the value of justice, especially from the economic aspect, because the regulation of the pre-emptive policy model of community policing (Polmas) which is regulated in the Regulation of the Chief of the National Police of the Republic of Indonesia Number 3 of 2015 concerning Community Policing (Polmas), has not regulated operational costs that should be allocated in order to carry out Polmas duties. Obstacles in the current pre-emptive law enforcement efforts to prevent terrorism crimes based on the value of justice are related to obstacles from legal substance, which include: unregulated operational costs, infrastructure, career path coaching, and reporting systems for Bhabinkamtibmas members.